In situ flow pair distribution function analysis to probe the assembly–disassembly–organisation–reassembly (ADOR) mechanism of zeolite IPC-2 synthesis. Issue 24 (25th October 2021) - Russell, Samantha E.; Henkelis, Susan E.; Vornholt, Simon M.; Rainer, Daniel N.; Chapman, Karena W.; Morris, Russell E.
Abstract : A four step mechanism for the disassembly and organisation stages of the ADOR process was determined using in situ flow pair distribution function. Abstract : The assembly–disassembly–organisation–reassembly (ADOR) process is an important tool to access zeolite structures that are otherwise unfeasible via hydrothermal methods. In situ flow pair distribution function (PDF) analysis has been used to probe the mechanism of the disassembly and organisation steps, with the disassembly a rapid step that is often difficult to capture. Zeolite UTL was hydrolysed by 6 M hydrochloric acid, with PDF measurements used to monitor framework alterations as the reaction proceeded. The resulting disassembly mechanism shows an initial rapid removal of germanium from the germanium-rich double 4 rings (d4r), followed by silicon rearrangement and gradual silanol condensation to form IPC-2P.